What is Responsible for India's Sharp Disinflation? - Chinoy, Sajjid (IMF Working Papers; Working Paper, 2016)
We analyze the dramatic decline in India's inflation over the last two years using an augmented Phillips Curve approach and quantify the role of different factors. Our results suggest that, contrary to popular perception, the direct role of lower oil prices in India's disinflation was relatively modest given the limited pass-through into domestic prices. Instead, we find that inflation is a highly persistent process in India, reflecting very adaptive expectations and the backward looking nature of wage and support price-setting. As a consequence, we find that a moderation of expectations, both backward and forward, and a rationalization of Minimum Support Prices (MSPs), explain the bulk of the disinflation over the last two years.